Application of the Islamic legal maxim “hardship begets ease” to mitigate hardship in the religious practices of the elderly Muslims - Karim, Fatimah (IIUM Press, 2025)
The elderly people occupy a revered status in Islamic tradition, with specific guidelines designed to protect their dignity and well-being. However, there is a significant gap in understanding how Islamic jurisprudence (fiqh) accommodates the physical and mental challenges that elderly Muslims face in fulfilling their religious obligations. This study aims to explore how Islamic law applies the maxim of al-mashaqqah tajlib al-taysīr (hardship begets ease) to mitigate these challenges, enabling elderly individuals to maintain their spiritual practices without undue burden. Utilizing an inductive, descriptive, and analytical methodology, the study investigates how this legal maxim is applied in key areas of worship—ṭahārah (purification), ṣalāh (prayer), ṣawm (fasting), and ḥajj (pilgrimage)—to accommodate the specific physical and cognitive challenges faced by elderly Muslims. One important finding reveals that Islamic jurisprudence is both compassionate and adaptable, offering specific rulings and allowances that cater to the diverse needs of elderly Muslims. The significance of this study lies in its potential to enhance the understanding and application of Islamic jurisprudence in addressing the practical religious needs of the elderly, ensuring they can fulfill their obligations with dignity and ease